Differences in physical activity behaviors of university women from rural, micropolitan, and metropolitan areas - Goodman, Blake D. (Kansas State University, 2020)
Background: Significantly fewer rural adults than urban adults meet physical activity (PA) guidelines, making rural adults one of the most physically inactive populations (only 19.4% meet PA guidelines). Women are also less physically active than men (20.1% versus 28.8% meet PA guidelines). Rural women identify numerous PA barriers in adulthood, many of which are community-related. In childhood, rural girls are less active than both their male and urban counterparts, and overall, PA declines from adolescence into adulthood. Many past studies have examined how PA behaviors change in college-aged populations, though few have shown how a student’s past environment may relate to their current behavior. Because barriers for rural women are rooted in their community, the social ecological model (SEM - based on the idea that the environment shapes behaviors) may be useful to categorize barriers and facilitators to PA. Purpose: To test for differences in current self-reported PA levels among university women from metropolitan, micropolitan, and rural areas, as well as gather insight into barriers and facilitators for PA within the first four levels of the SEM (both in high school and in the university setting). Women from rural areas were hypothesized to report less PA and more barriers to PA than those from metropolitan and micropolitan areas both in high school and in the university setting. Methods: Inclusion criteria were women age 18-24, attended in-person classes at a US university, and were not collegiate athletes or had an injury/disability that hindered the ability to do PA. Women respondents (n=371) provided demographic information, self-report PA via the international physical activity questionnaire (IPAQ, long form), and both scaled (scale: 1 – strongly disagree to 5 – strongly agree) and summed responses for barriers and facilitators to PA. Data were analyzed by Kruskal-Wallis H tests and Mann-Whitney U tests to examine differences between Rural Urban Commuting Area (RUCA) groups – metropolitan, micropolitan, and rural. Results: Respondents were a mean age of 20.0 years (SD = 1.2 years), mostly white (84.5%), not Hispanic or Latino (91.1%), and were categorized into a RUCA group [metropolitan (n = 258), micropolitan (n = 41), and rural (n = 65)] based on high school ZIP codes. No significant differences were found between groups for total PA (Median: 2007.5 MET-min, IQR: 568.9-5035.5 MET-min) or intensity-specific PA. Recreational vigorous activity was statistically significantly different by Mann-Whitney U test (U = 224.5, p = 0.012), in which participants from rural areas reported significantly more recreational vigorous activity than participants from micropolitan areas. A statistically significant difference was found for recreational walking, in which micropolitan participants did less recreational walking than rural participants (KW: ꭓ2(2) = 7.525, p = 0.023; U=394.0, p = 0.006). Statistically significant differences for access to resources (KW: ꭓ2(2) = 17.543, p < 0.001) and perceived PA resources in the high school community (KW: ꭓ2(2) = 23.138, p < 0.001) were found, in which rural participants reported less access to resources than both micropolitan (U = 621.5, p = 0.001) and metropolitan (U = 4328.5, p < 0.001) participants and fewer perceived resources than both micropolitan (U = 539.0, p < 0.001) and metropolitan (U = 3600.5, p < 0.001) participants. Discussion: The hypothesis that rural women would report less PA was not supported in this study. Women from rural areas identified as having less access to PA resources in their high school setting, which is consistent with previous literature among adult rural women. Yet, they reported significantly greater recreational PA than those from micropolitan areas. Future research should investigate whether PA is more influenced by past PA behaviors and environments or the current environment in which participants live.
Keywords: Physical activity; Rural urban commuting area codes; Rural; Metropolitan; International physical activity questionnaire; Physical activity behaviors